Effects of Er stabilization on thermal property and failure behavior of Gd2Zr2O7 thermal barrier coatings. (June 2021) - Shen, Zaoyu; Liu, Guanxi; Mu, Rende; He, Limin; Xu, Zhenhua; Dai, Jianwei
Highlights: The GdErZrO coating exhibit a high thermal expansion coefficient and low thermal conductivity. The as-deposited TBCs show a high thermal life and a good microstructure stability at 1100 °C. The element diffusion might be critical factor for cracks extension leading to the TBCs failure. Abstract: This work focuses on the effects of Er stabilization on thermal property and failure behavior. The GdErZrO/YSZ TBCs exhibit a defect fluorite structure with high thermal expansion coefficient and low thermal conductivity. The as-deposited TBCs show a high thermal life and a good microstructure stability at 1100 °C due to the Er stabilization and the feathery microstructure. After thermal cycling test, the broken of thermally grown oxide is generally attributed to the Al2 O3 growth and cracks evolution. Furthermore, the element diffusion might be critical factor for cracks extension leading to the spallation and delamination failure.